Modification Collapsible Pot on Blue Swimming Crab (Portunus sp.) Fisheries in Northern Pemalang Waters, Central Java - Zulkarnain Zulkarnain; Ronny Irawan Wahju; Tigor Wahyudi; Fis Purwangka; Dwi Putra Yuwandana (ALBACORE Jurnal Penelitian Perikanan Laut, 2019)
This research uses collapsible pots from the modified of collapsible pots belong local fishermen who have two doors becomes single door (as treatments), but its have measure four times bigger than fisherman’s collapsible pot. The aim of this study is to compare the catch composition of blue swimming crab such as the quantity, carapace length and weight, catch worthiness and productivity of modification collapsible pots compare with the fisherman's collapsible pot as a control. This study used 2 treatments, 15 pairs of collapsible pots in each treatment and 20 repetitions. The results showed that the control collapsible pots have caught of blue swimming crab 159 individuals and weighing 19.1 kg, while the modification collapsible pots have 128 individuals and weighing 15.06 kg. Modification collapsible pots have catch worthiness 97% more catchability compared to 84% of control collapsible pot. Results of the statistical tests shows that the blue swimming crabs catch have no significant effect in weight (kg) but its have a significant effect on the number (individual). The total value of productivity that control collapsible pot is greater than modification collapsible pot. Key words: blue swimming crab, modification collapsible pot, productivity